Associated Hematolymphoid Malignancies in Patients With Lymphomatoid Papulosis: A Canadian Retrospective Study. Issue 3 (November 2017) - AbuHilal, Mohanad; Walsh, Scott; Shear, Neil
Background: Lymphomatoid papulosis is one of the primary cutaneous CD30+ T-cell lymphoproliferative disorders. Although considered a benign disease, lymphomatoid papulosis has been associated potentially with an increased risk of secondary hematolymphoid malignancies. Objective: The aim of this study was to assess the clinical characteristics and histologic subtypes of lymphomatoid papulosis, identify the prevalence and types of secondary hematolymphoid malignancies, and determine the potential risk factors for development of these hematolymphoid malignancies. Methods and Materials: A retrospective chart review was performed for all histologically confirmed cases of lymphomatoid papulosis between 1991 and 2016. Results: Seventy patients with lymphomatoid papulosis were identified. Thirty patients (43%) experienced a secondary hematolymphoid malignancy. Twenty-four (80%) of the hematolymphoid malignancies occurred after the onset of lymphomatoid papulosis. Older age at diagnosis of lymphomatoid papulosis, male sex, histology type B, and the presence of T-cell receptor gene rearrangement are associated with higher risk of developing hematolymphoid malignancy. Conclusion: Lymphomatoid papulosis is associated with increased risk of developing secondary hematolymphoid malignancies, particularly mycosis fungoides and cutaneous anaplastic large cell lymphoma.